Protecting the Labour Rights of Young People as a Special Area Body Field - kyzy, Bayjanova Ramuza Tenelbay (European Journal of Life Safety and Stability (2660-9630), 2022)
It covers a set of issues related to the support of youth employment and explains the different sections of labor law, such as employment contracts, working hours, as well as time off. At the same time, information was provided on occupational safety and health procedures and restrictions, as well as important provisions of the regulations on occupational safety and health in international agreements.